Properties and observables of massive galaxies in self-interacting dark matter cosmologies - Mastromarino, Claudio; Despali, Giulia; Moscardini, Lauro; Robertson, Andrew; Meneghetti, Massimo; Maturi, Matteo (Monthly notices of the Royal Astronomical Society, 2023)
We use hydrodynamic cosmological simulations to test the differences between cold and self-interacting dark matter models (CDM and SIDM) in the mass range of massive galaxies (1012 < M200/M⊙ h−1 < 1013.5). We consider two SIDM models: one with constant cross-section $σ /m_{χ } = 1\, \mathrm{cm^2 \, g^{-1}}$ and one where the cross-section is velocity-dependent. Despite a weak trend in mass, we find that with the inclusion of baryons the differences between SIDM and CDM density profiles observed in the dark-matter-only case are almost erased. We also search for signatures of SIDM in the distribution of strong lensing Einstein radii and find that the distributions derived from CDM and SIDM hydro runs are both comparable to observational samples of strong lenses. We find that, looking at the total matter distribution, the interplay between self-interactions and baryons can greatly reduce the expected differences between CDM and SIDM models at this mass scale, making the discrimination between these DM models challenging. However, looking at the dark matter/baryonic fractions in the inner region of the haloes we show that the deviations of SIDM from CDM can still be found considering these components separately. These results highlight that one of the most promising paths to discriminate between CDM and SIDM is to focus on techniques able to distinguish between the dark matter and baryonic components in galaxies and clusters.